The Relationship Between Knowledge of Clean and Healthy Living Behavior (CHLB) and Healthy Living Behavior Among Elementary School Students at Public Elementary School 5 Katerban, Baron District - Leili Setiawan Rosyid; Fitra Handika Hutama (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2025)
Introduction: Clean and Healthy Living Behavior (CHLB) is an effort to prevent diseases by implementing healthy habits from an early age. Elementary school children are a vulnerable group to health problems, thus requiring the inculcation of knowledge and behavior related to CHLB. Objectives: This study aims to determine the relationship between knowledge of CHLB and healthy living behavior among elementary school students at Public Elementary School 5 Katerban, Baron District. Methods: This study employed a correlational analytic design with a cross-sectional approach. The population consisted of all students in grades I–VI (62 students) with a total sampling technique. Instruments included a CHLB knowledge questionnaire and a healthy behavior observation sheet. Data were analyzed using the Chi-Square test. Results: The results showed that most students had good knowledge (61.3%), while healthy living behavior in the good category was 58.1%. The Chi-Square test yielded p = 0.021 (<0.05), indicating a significant relationship between CHLB knowledge and healthy living behavior. Conclusions: Knowledge of CHLB is associated with healthy living behavior among elementary school students. The role of teachers, parents, and health workers is needed to enhance CHLB education through creative and continuous methods.